Evaluation of Employee Performance in the Implementation of UPT Inpatient Services. Gunung Tinggi Health Center in Deli Tengah Regency - Tariolan Tarigan; Warjio Warjio; Adam Adam (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study aims to evaluate the performance of employees in improving inpatient services at UPT. Gunung Tinggi Health Center, Deli Serdang Regency. Employee performance greatly affects the quality of services received by the community. The research method used is qualitative descriptive, with an in-depth interview, observation, and documentation approach to collect data. The research informants consisted of the head of the Health Centre, medical personnel, and inpatients who provided views related to the service. The results of the study show that inpatient services at the Health Centre have been running well with clear standard procedures, although there are still challenges in the limitations of facilities and infrastructure. High employee performance, including discipline and motivation, has contributed to community satisfaction, although some constraints related to the facilities and location of the Puskesmas need to be improved. This research provides an overview of the importance of employee performance management in maintaining the quality of public services and enhancing the public's perception of Puskesmas.